2016
DOI: 10.1116/1.4958793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the osseointegration of nanostructured titanium implants in animal models: Current experimental methods and perspectives (Review)

Abstract: The aim of this paper is to review the experimental methods currently being used to evaluate the osseointegration of nanostructured titanium implants using animal models. The material modifications are linked to the biocompatibility of various types of oral implants, such as laser-treated, acid-etched, plasma-coated, and sand-blasted surface modifications. The types of implants are reviewed according to their implantation site (endoosseous, subperiosteal, and transosseous implants). The animal species and targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…Hulbert S. et al demonstrated that osteons require mini pores in which the diameters range from 150 to 200 µm [ 46 ]. Later, Babuska V. found that lamellar bone and bone remodeling were highly favored by 200-µm pores created by a laser compared to 10–25-µm pores [ 47 ]. However, Stangl R et al conducted histological analysis and determined that the optimal implant surface showed wavy structures with an average wavelength of 11.6 µm and with deviations in height of 1.4 µm [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hulbert S. et al demonstrated that osteons require mini pores in which the diameters range from 150 to 200 µm [ 46 ]. Later, Babuska V. found that lamellar bone and bone remodeling were highly favored by 200-µm pores created by a laser compared to 10–25-µm pores [ 47 ]. However, Stangl R et al conducted histological analysis and determined that the optimal implant surface showed wavy structures with an average wavelength of 11.6 µm and with deviations in height of 1.4 µm [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy is to improve the osteoinductive properties of Ti implants to activate the TGF-β/BMP and non-canonicalWNT/Ca 2+ (WNT5A, FZD6) pathways directly by modified surface structures as shown by Chakravorty et al [ 135 ]. Especially in vitro results require highly standardized animal models to receive reliable data [ 136 ].…”
Section: Titanium Surface Properties and Osteointegrationmentioning
confidence: 99%
“…In concordance with our results [ 16 ], Thirugnanam et al [ 17 ] found significantly higher adhesion of osteoblasts and increased bone formation on nanostructured titanium surfaces when compared to conventional titanium. Since that time, many in vitro as well as in vivo studies have investigated the impact of nanostructured surfaces on the behavior of the surrounding cells [ 18 , 19 ]. Zhou et al [ 20 ] suggested one possible explanation, based on changes in the chemical composition of titanium surface immersed in a simulated body fluid (SBF) with an addition of bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%